Operational Cost Comparison of Several Pre-Treatment Techniques for OMW Treatment - Coskun, Tamer; Debik, Eyup; Demir, Neslihan Manav (WILEY, 2012)
Olive mill wastewaters (OMWs), which are known to have deep impacts on the receiving water bodies due to their high-strength contents of organic materials and color, must be treated before discharge. For this reason; a number of research studies have been available in current literature related to the treatment of OMWs. However, no widely accepted treatment alternatives have been proposed yet. The common results of these studies suggest that OMWs must be pretreated prior to final purification processes. This study focuses on the comparison of alternative pre-treatment processes in the aspect of chemical oxygen demand (COD) removal and costs of operation. Centrifuging, lime precipitation, acid cracking, and electrocoagulation processes were performed to compare removal efficiencies and operational costs. The COD removal efficiencies for centrifuging, lime precipitation, acid cracking, and electrocoagulation processes were determined to be 30.1, 24.1, 20.0, 53.7%, respectively, with operational costs being $0.30, $0.37, $1.42, and $11.60 per cubic meter of wastewater treated, respectively. The centrifuging process was concluded to be the most appropriate one according to the COD removal efficiency and cost of operation.
Keywords: Acid cracking; Centrifuging; Electrocoagulation; Lime precipitation; Olive mill wastewater; MILL WASTE-WATER; OLIVE-MILL; DETOXIFICATION; DEGRADATION; FENTON; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources